A pilot study on the advancement of livestock healthcare bio-capsules and development of customized long-range network in the United Arab Emirates - Khaja Mohteshamuddin; Heejin Kim; Seunghwan Lee; Hanseok Kang; Leo Marlon Estrada; Muhammad Faisal Nadeem; Mohamed Elfatih Hamad; Abdullah Dakheel (Smart Agricultural Technology, 2023)
The UAE's environment is characterized by low rainfall, high temperatures, poor soil and lack of natural waterways. The country has been making tremendous efforts to build a sustainable agricultural and animal wealth sector that is better able to contribute to its national agenda of food security. Commercial cattle farming in such challenging conditions would require an effective disease prediction and warning system for optimizing the production dynamics. Therefore, we are proposing the use of smart livestock system comprising of orally ingested bio-capsules for monitoring the livestock health, connected through a customized long-range network (430 MHz) in the United Arab Emirates, which monitors the real time animal body condition data (temperature and body activity) using a mobile or web-based application. The study demonstrated a 100% success rate in estrus alarms in the test animals, 61.29% for calving alerts and an accurate disease prediction warning in all the animals diagnosed unhealthy. the conception rate in these estrus diagnosed animals with artificial insemination was 61.53%, which was significantly higher than the conception rate in the absence of this detection technology at the farm. The capsule was well tolerated in all the test animals and did not show any acute adverse or allergic reactions. This is the first of its kind of study using these advanced bio-capsules and development of the customized long-range network in the United Arab Emirates for smart livestock healthcare management.